Fabrication of MWCNT/S/AC Battery Electrodes Using the Doctor Blade Method with Cyclic Voltammetry (CV) Testing of KCL Electrolyte Variations to Determine Specific Capacitance Values (International Journal of Scientific Research in Science and Technology, 2025)
The increasing demand for energy storage has led researchers to try to find cathode materials that have the ability to increase specific capacitance. Sulfur-based electrodes are considered the right choice to overcome this problem; however, there are still weaknesses due to the insulating properties of sulfur and polysulfides. This study uses MWCNT and activated carbon materials, which are considered to be able to increase conductivity and minimize sulfur dissolution into the electrolyte, which affects the specific capacitance value. Electrolytes as a means of ion transport also greatly affect the performance of battery electrodes. Electrochemical analysis was carried out by conducting CV tests using KCl electrolyte solutions at concentrations of 0.05 M, 0.25 M, and 0.5 M. The results showed that the use of KCl electrolyte solutions on the electrodes showed an increase in specific capacitance values along with increasing electrolyte concentrations. With each concentration, the specific capacitance values were 0.1725 F/g⁻¹, 0.3593 F/g⁻¹, and 0.5336 F/g⁻¹.